HUBUNGAN MANAJEMEN ENERGI DENGAN KELELAHAN PADA PASIEN DIABETES MELITUS TIPE 2 - Nisrina Na'ilah Rahmatika; Jon Hafan Sutawardana; Mulia Hakam (Universitas Prima Indonesia, 2022)
Metabolic disorders in blood sugar levels are caused by damage to insulin secretion so that it affects energy production. Fatigue is one of the complaints and symptoms of Diabetes Mellitus (DM) patients. This study aims to analyze the relationship between energy management and fatigue in patients with diabetes mellitus. This study used a correlational design with a cross sectional approach. Calculation of the sample in this study using the Slovin formula, which obtained 34 respondents with diabetes mellitus at the Kejayan Health Center, Pasuruan Regency using purposive sampling technique. Data collection in this study used an energy management questionnaire and Multidimensional Fatigue Invantory (MFI20). The results show that in energy management, energy management in patients with diabetes mellitus is obtained with a good category of 55,9%. On fatigue, the median result is 60.50 with a min-max value of 34-73. The correlation test showed that there was a relationship between energy management and fatigue (p = 0,033, r = -0,366, = 0,05). There is a negative correlation which shows that the higher the energy management, the lower the fatigue felt. Fatigue felt by diabetic patients does not go away easily so that energy management must be carried out properly. It is expected that diabetes mellitus patients maintain good energy management. It is a concern for nurses in improving energy management of diabetes mellitus patients to reduce the fatigue they feel.